The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2014
DOI: 10.1177/0020764014560595
|View full text |Cite
|
Sign up to set email alerts
|

Trust and quality of life: A cross-sectional study of young women

Abstract: Policies are needed to improve participation and reciprocity at the level of individuals and informal social groups, including local to broader communities in order to increase the sense of community belonging, improving trust and consequently quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 32 publications
(42 reference statements)
2
19
0
Order By: Relevance
“…The correlations between residents' characteristics and well‐being outcomes have been reported in another paper (Salehi et al . ). Correlations of living environment variables with variables for lifestyle behaviours and well‐being are presented in Table .…”
Section: Resultsmentioning
confidence: 97%
“…The correlations between residents' characteristics and well‐being outcomes have been reported in another paper (Salehi et al . ). Correlations of living environment variables with variables for lifestyle behaviours and well‐being are presented in Table .…”
Section: Resultsmentioning
confidence: 97%
“…Previous studies showed that social capital was positively associated with quality of life in the elderly [ 39 41 ], adults [ 42 ], long-term social assistance [ 43 ], patients with fibromyalgia [ 44 ], multiple sclerosis patients [ 45 ], women [ 46 , 47 ], and AIDS patients [ 33 ]. In this cross-sectional study, we found some consistent evidence to support the hypothesis that higher cognitive social capital was associated with higher PCS and MCS, the two domains of quality of life, after adjustment for SES and risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…In the context of healthcare decision, formation of trust is undoubtedly a strong influential factor for QHL. However, the causal association between trust and well-being outcomes has yet to be examined comprehensively (Salehi et al 2015). However, a positive association of QHL is found with higher education, having affluence and sturdy social capital components including trust solidarity (Himanshu, Arokiasamy, and Talukdar 2019).…”
Section: Theoretical Framework and Hypothesis Developmentmentioning
confidence: 99%